ANALISIS SISTEM PENGENDALIAN INTERN PIUTANG PADA CV. CAHAYA NIAGA TANI - Putri Ramadanty (Jurnal Ilmiah Ekonomi Global Masa Kini)
The purpose of this is to analyze and know how to receivable control system at CV. Cahaya Niaga Tani Palembang has done well to reduce the misuse of cash in order to minimize loses anad provide accurate information for the control of the company. In this study, researchers used a method of analysis qualitative. Analyzes were performed using the information, adescription in the form language of prose or standard language, then linked with other data to obtain clarity on the truth or otherwise, so as to obtain an overview of new and strengthen a picture already there and vice versa. The type of data used are primary data and secondary data collection techniques used interviews, documentation, library research. The results of this study is expected to provide accurate information on accounts receivable control system so that the CV. Cahaya Niaga tani Palembang can better control the accounts again and runs as expected.